Efforts to Increase Reuse Intention with the TAM Model for Multi-Service Application Users - Sumar Sumar; Indah Noviyanti; Novita Herlissha; Dini Oktariani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
As time advances, humans need technology as a tool to help and facilitate all their activities in daily life, one of which is in the fields of transportation or food. In Indonesia, technological developments in the transportation sector can be seen from the rapid development of the Grab application. Through the Grab application, initially OVO was only used by the public as a payment method for Grab's transportation services. But now consumers can carry out various activities ranging from transportation to ordering food. This phenomenon illustrates how the Grab application with a payment system via OVO can be massively accepted by the Indonesian people. Acceptance of this technology can be analyzed using the Technology Acceptance Model (TAM). When using technology, people do not always receive the benefits, accept the convenience, and fully accept the risks, but often there is resistance or mistakes often occur. Therefore, this research aims to analyze the influence of the Technology Acceptance Model (TAM) with the variables perceived usefulness, perceived ease of use, and Perceived Risk in Grab application users on Reuse Intention. The population of this study were all Grab application users in Pangkalpinang City, with purposive sampling involving 112 respondents whose characteristics of application users ranged from 18-50 years and had also used the OVO feature for at least 1 year. The analytical method that will be used to analyze the data is SPSS 26.0. The results of this research explain that the variables perceived usefulness, perceived ease of use, and Perceived Risk have an influence on Reuse Intention.